Application of Adaptive Sliding Mode Control with an Ellipsoidal Sliding Surface for Vehicle Distance Control - Taichi Mizoshiri; Yasuchika Mori (SICE Journal of Control, Measurement, and System Integration, 2017)
This paper proposes a sliding mode control with an ellipsoidal sliding surface for vehicle distance control. The performance of two different sliding surfaces, namely ones that are ellipsoidal and linear, is evaluated under the same conditions. Each controller, regardless of sliding surface, is designed to achieve a similar level of control performance. It is shown through simulation that the sliding mode control with the ellipsoidal sliding surface proposed by the authors has advantages over conventional sliding mode control with a linear sliding surface, in that it is smoother and has lower energy consumption. Furthermore, a boundary layer width adaptation law is applied to prevent chattering.